მცენარეთა ლათინური სახელების ქართულად გადმოტანის თავისებურებანი - ჩოთალიშვილი, ლელა; ჭელიძე, დავით; ხოჭოლავა-მაჭავარიანი, ნანა (ლოგოსი, 2023)
Latin and ancient Greek are the basis on which new international botanical terminology is built and on which the established one is refined. For the correct translation of the scientific names of plants from Latin into Georgian and their correct spelling, along with taking into account the established rules, it is often necessary to develop new recommendations and change the already established forms. At this time, the data of the Latin and Georgian languages ​​should be verified; It is necessary to take into account the features and patterns of both languages; As well as news of international botanical nomenclature etc. During the work on “Latin-Georgian Dictionary of Plant Names” and “Accumulative Glossary of Plant Names”, based on linguistic and philological analysis, we have developed rules for translating Latin phytonyms into Georgian and made some changes: Replacement of obsolete Latin phytonyms with modern nomenclature. Clarification of the Georgian name of some taxonomic units from the point of view of the generic relationship. Correction of incorrect spelling. The specificity of the translation of some features of Latin phytonyms into Georgian. The peculiarity of the Georgian vocabulary is taken into account and a creative approach is applied. Accounting for the history of the origin of some phytonyms. Epithets comprised of two words were fused into one word by suppressing the hyphen, thus merging the two words and abiding by the norms of Georgian scientific language. When importing generic and specific names, we have taken into account the phonetic rules and specific pronunciation of the language of origin, the translation practices from these languages to Georgian, as well as the etymology of the phytonyms.